Synthesis, thymidine phosphorylase inhibitory and computational study of novel 1, 3, 4-oxadiazole-2-thione derivatives as potential anticancer agents. (October 2018) - Bajaj, Shalini; Roy, Partha Pratim; Singh, Jagadish
Graphical abstract: Highlights: Synthesis of some 1, 3, 4-oxadiaozle-2-thione derivatives. The synthesized compounds were evaluated for their anticancer activity. Among the synthesized compounds, 2 j showed significant cytotoxic activity against MCF-7 cell line. ADMET properties of all the synthesized were predicted. Abstract: A series of novel 1, 3, 4-oxadiazole-2-thione derivatives were designed, synthesized and evaluated for in vitro anticancer activity against breast cancer (MCF-7) cell line and thymidine phosphorylase. The synthesis of target compounds was performed by cyclization reaction using aromatic amines and carbon disulphide to get mannich bases. The synthesized compound 2 j exhibited the most potent anticancer activity against MCF-7 cell line. Compounds 2d, 2j, 2o and 2h showed potent thymidine phosphorylase inhibitory activity. The SAR study revealed that the substitution of phenyl ring with electron withdrawing group at R 1 position and less bulky amines group at R 2 position of 1, 3, 4-oxadiazole-2-thione ring showed significant growth inhibitory activity. Further in silico ADMET properties of synthesized compounds were calculated along with molecular docking to study the binding mode of the compounds in the active site of thymidine phosphorylase (TP). The molecular docking studies showed that amines group have good binding interaction on active site residues of TP such as compounds 2j and 2o exhibited hydrogen bond interaction with amino acid residues GLY152, THR151 and HIS116 of thymidine phosphorylase (PDB ID: 1UOU ). The result of biological activity and docking study revealed that amines group at R 2 point of 1, 3, 4-oxadiazole-2-thione moiety is essential for anticancer activity.